Peningkatan Kemandirian Ekonomi Masyarakat Melalui Manajemen Pemanfaatan Teknologi Pertanian Ramah Lingkungan - Chris N. Namah; Jemseng C. Abineno (Jurnal Administrasi Terapan, 2024)
Increasing community economic independence through agricultural technology is not only related to increasing production and income, but also community empowerment. By mastering technology, farmers can manage their resources more effectively, reduce dependence on outside parties, and create added value from their agricultural products. Apart from that, good technology management can also reduce negative impacts on the environment, support sustainable agriculture, and ultimately improve the quality of life of society as a whole. Adoption of agricultural technology can also create new jobs in rural areas, for example through the development of technical services, digital marketing and processing of agricultural products. In this way, technology is not only a tool to increase agricultural efficiency, but also a driving force for a sustainable local economy. The aim of the research is to describe an overview of the use of agricultural technology through the application of water-saving and environmentally friendly agricultural technology and to realize community economic independence and preserve natural resources (soil nutrients). The research was carried out at the Tnao Mat Farmers' Group Garden, III Bieto Hamlet, Niuk Baun Village, West Amaraasi District, Kupang Regency. The data collection methods used were observation, interviews and documentation. Next, experiments were carried out to produce Organic Fertilizer. The results obtained are that the environmentally friendly agricultural model has strengths greater than its weaknesses, as well as its opportunities greater than its threats. So farmers can be directed to dare to try environmentally friendly agricultural models to reduce production costs and increase quality agricultural products. Keywords: Independence, Economy, Technology, Agriculture, Environmentally Friendly